Termites (Insecta : Isoptera) from Haryana, with New Distributional Records - Thakur, R. K. (Indian Forester, 2007)
Twenty species of termites belonging to three families (Kalotermitidae, Rhinotermitidae and Termitidae) and ten genera (Neotermes, Bifiditermes, Heterotermes, Coptotermes, Speculitermes, Eremotermes, Microcerotermes, Odontotermes, Microtermes and Trinervitermes) are reported here from Haryana. Nine termite species (Neotermes fletcheri, Coptotermes heimi, Speculitermes cyclops, Eremotermes paradoxalis, Odontotermes assumuthi, Odontotermes indicus, Odontotermes redemani, Odontotermes wallonensis and Trinervitermes biformis) are being reported for the first time from Haryana.